Association of sex hormones with hepatic steatosis in men with chronic hepatitis B. Issue 3 (March 2022) - Chen, Qingling; Zhao, Lili; Mei, Ling; Zhong, Rui; Han, Ping; Yang, Hang; Li, Qian; Li, Jia
Abstract: Background: No study on the relationship between hepatic steatosis and sex hormone levels in male patients with chronic hepatitis B (CHB) infection has been conducted. Aims: We aimed to investigate the association between serum sex hormones and hepatic steatosis among a cohort of males with CHB. Methods: In this cross-sectional study, 268 male patients with CHB were enrolled. All participants underwent anthropometric measurement, blood testing, and FibroScan test. Multiple logistic regression analysis was used to investigate the association of serum sex hormones with hepatic steatosis. Results: We included 137 males with and 131 without hepatic steatosis in this study. Subjects with serum testosterone (T) levels in the highest tertile had an odds ratio (OR) (95% confidence interval [CI]) of 0.35 (0.18–0.70) ( P for trend=0.003); those with serum prolactin (PRL) levels in the highest tertile had an OR (95%CI) of 0.21 (0.10–0.45) ( P for trend<0.001); and those with serum estradiol/testosterone (E2/T) in the highest tertile had an OR (95%CI) of 4.02 (1.97–8.20) ( P for trend<0.001) for hepatic steatosis. Conclusion: Lower serum total T and PRL levels and higher total E2/T are independently associated with presence of hepatic steatosis in male patients with CHB.